Factors influencing physical activity among individuals with lower limb amputations: a qualitative study. Issue 9 (24th April 2023) - Lee, Leanna S.; Hitzig, Sander L.; Mayo, Amanda; Devlin, Michael; Dilkas, Steven; MacKay, Crystal
Abstract: Purpose: The purpose of this study was to explore the barriers and facilitators to physical activity from multiple stakeholder perspectives including individuals with LLA and health professionals. Materials and methods: A qualitative descriptive study situated within an interpretive research paradigm was conducted. Semi-structured interviews were held with individuals with LLA recruited from rehabilitation hospitals in a metropolitan city in Canada. Health professionals with experience in amputation care were recruited from across Canada. Data were analysed using codebook thematic analysis. Results: Thirty-three individuals with LLA and eighteen health professionals participated. Six themes were generated which represent the perceived barriers and facilitators to physical activity. Themes including Informal and Formal Supports, Availability of and Access to Community Resources, and Fit and Function of the Prosthesis were perceived by many individuals as facilitators, while acting as a barrier for others depending on an individual's circumstances. Conclusions: These findings provide us with a basis of understanding from which we can begin addressing barriers to physical activity for individuals with LLA, in support of developing patient-centred interventions and physical activity programs for this population. IMPLICATIONS FOR REHABILITATION: Irrespective of amputation etiology, individuals who have lower limb amputation experience several barriers to engaging in physical activity. Many system-level barriers to physical activity exist for people with lower limb amputation, which include lack of availability and access to community resources and specialised prostheses conducive to physical activity participation. A participatory approach engaging both patients and rehabilitation professionals can address the patient-provider discordance with respect to a patient's motivation and attitude towards physical activity participation by creating a supportive environment conducive to behaviour change. The development of future, patient-centered interventions, and physical activity programs for individuals with lower limb amputation must consider fear of falling as a prominent barrier to physical activity and devise potential strategies to address this barrier, by setting realistic and actionable goals.